INOVASI TEKNOLOGI TEPAT GUNA UNTUK MENINGKATKAN PRODUKTIVITAS, NILAI TAMBAH DAN AKSES PASAR USAHA MIKRO DI UNIT PERMUKIMAN TRANSMIGRASI â€œKARANG CAHYOâ€ KABUPATEN BENGKULU SELATAN - Slamet Widodo, Soengkono; S. Hindarto, Kanang; Widodo, Slamet; Mujiharjo, Sigit (JURNAL EKOMBIS REVIEW, 2015)
Soengkono, Kanang S. Hindarto, Slamet Widodo, Sigit Mujiharjo; The objective of the first research is to know: (1) the background of economic factors of transmigrant, (2) the natural resources potency, (3) the human resources of transmigrant potency, (4) the analysis of business environment, (5) the model micro business development, (6) the build of micro business group, (7) the formulation model based on human and natural resource potency with simple and accepted technology, (8) the practice of simple and accepted technology, (9) the practice of marketing, and (10) the training of small/micro business management. The result of the research is identified that: (1) the transmigrant society have a high motivation to stay at location study, (2) the transmigrant society wish to facilitation in economic development to income generating, (3) the transmigrant society zeal for to follow research program conducted by researcher, (4) have been build of small business group, (5) have executed of simple and accepted technology test-drive, (6) have executed of training of small business management, (7) marketing management. In general the model based on human and natural resource potency with simple and accepted technology have been increase of income generating of transmigrant.Key Word: Transmigrant, Micro Business Development, Simple and Accepted Techology, Productivity, Value Added, Market Access, and Incoming Generating